2000
DOI: 10.1159/000012132
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin-Gemcitabine Treatment of Patients with Transitional Cell Carcinoma of the Bladder and Impaired Renal Function

Abstract: Introduction: Bladder cancer is a frequently occurring tumour in Spain and usually affects elderly patients with renal impairment. The development of new combination therapies for such patients is thus of vital importance. Patients and Methods: Between 1997 and 1998, 17 patients with locally advanced non-surgical or metastatic bladder tumours were treated at our centres. Treatment consisted of 1,000 mg/m2 of gemcitabine administered on days 1 and 8, and carboplatin (area under the concentration curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 8 publications
7
31
0
Order By: Relevance
“…Others studies combining gemcitabine and carboplatin demonstrated similar activity with manageable toxicity when they were used as first-line treatment of advanced bladder carcinoma in the elderly and those unfit for cisplatin-based chemotherapy. Therefore, it may be concluded that this combination of Gemox represents a reasonable choice for the treatment of such patients [11,12]. Despite the relatively poor clinical characteristics, the treatment was well tolerated.…”
Section: Discussionmentioning
confidence: 92%
“…Others studies combining gemcitabine and carboplatin demonstrated similar activity with manageable toxicity when they were used as first-line treatment of advanced bladder carcinoma in the elderly and those unfit for cisplatin-based chemotherapy. Therefore, it may be concluded that this combination of Gemox represents a reasonable choice for the treatment of such patients [11,12]. Despite the relatively poor clinical characteristics, the treatment was well tolerated.…”
Section: Discussionmentioning
confidence: 92%
“…[2][3][4][5][6] Notably, these trials employed heterogeneous eligibility criteria and most did not distinguish patients ineligible for cisplatin based on renal function alone from patients ineligible for other reasons (eg, poor performance status). This distinction is important, as the former group of patients may benefit from more aggressive carboplatin-based regimens, whereas the latter patients may not tolerate such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of doxorubicin was decreased by 20% for grade 4 mucositis. Dose modifications for paclitaxel plus carboplatin were as follows: if on the scheduled day of chemotherapy administration the absolute neutrophil count was <1000 cells/mm 3 or the platelet count was <100,000 cells/mm 3 , paclitaxel plus carboplatin was delayed for 1 week. If blood counts remained unsatisfactory after 2 1-week delays the patient was removed from the protocol.…”
Section: Toxicity/dose Modificationsmentioning
confidence: 99%
“…Carles et al (37) reported the results of a Phase II study of GCarbo, which consisted of 1000 mg/m 2 of gemcitabine on Days 1 and 8, and carboplatin with the area under curve (AUC) of 5 on Day 1 and every 21 days. The cCR of 17 patients participating in this study was between 20 and 55 ml/min.…”
Section: Modification Of Cisplatin-and Carboplatin-based Chemotherapymentioning
confidence: 99%